2018
DOI: 10.1073/pnas.1719070115
|View full text |Cite
|
Sign up to set email alerts
|

Plastid terminal oxidase requires translocation to the grana stacks to act as a sink for electron transport

Abstract: Abstract:The plastid terminal oxidase (PTOX) has been shown to be an important sink for photosynthetic electron transport in stress tolerant plants. However, overexpression studies in stress sensitive species have previously failed to induce significant activity of this protein.Here we show that overexpression of PTOX from the salt tolerant brassica species Eutrema salsugineum does not, alone, result in activity, but that over-expressing plants show faster induction and a greater final level of PTOX activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
2
27
0
1
Order By: Relevance
“…This leads to the conclusion that the photoactive PQ pool size per se has a limited influence on photosynthetic efficiency, and that the photosynthetic defect becomes symptomatic only when PQ limitation is associated with an additional impairment in its mobility. Impaired PQ mobility may be the cause affecting the reoxidation of the photoactive PQ by PTOX, since it may require an exchange between grana stacks and stroma lamellae ( Figure 6A; Stepien and Johnson, 2018). Furthermore, it would affect the exchange between the photoactive pool and the reservoir stored in the PGs necessary to maintain the photoactive PQ pool size (Pralon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the conclusion that the photoactive PQ pool size per se has a limited influence on photosynthetic efficiency, and that the photosynthetic defect becomes symptomatic only when PQ limitation is associated with an additional impairment in its mobility. Impaired PQ mobility may be the cause affecting the reoxidation of the photoactive PQ by PTOX, since it may require an exchange between grana stacks and stroma lamellae ( Figure 6A; Stepien and Johnson, 2018). Furthermore, it would affect the exchange between the photoactive pool and the reservoir stored in the PGs necessary to maintain the photoactive PQ pool size (Pralon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these findings, a recent study has shown the crucial role of PTOX in enabling growth under intermittent light conditions (Nawrocki et al , ). In model species, PTOX must be transferred to the grana to develop its photoprotective role (Stepien and Johnson, ). A recent study of plants originating from the Gurbantünggüt Temperate Desert (north‐west China) revealed an increased PQ pool oxidation and enhanced PSI activity when grown under high light, in comparison with Arabidopsis thaliana (Tu et al , ).…”
Section: Photobiochemistrymentioning
confidence: 99%
“…The low rate of electron flow sustained by PTOX ranges from 0.1 to 5 e 2 PSII 21 s 21 in the chloroplasts of plants and C. reinhardtii (Houille-Vernes et al, 2011;Trouillard et al, 2012), which does not qualify PTOX as an efficient electron sink. Despite its low reaction rate, PTOX has been suggested to play a photoprotective role when the light absorption by PSII exceeds the capacity of the downstream reactions (Carol et al, 1999;Niyogi, 2000;Ort and Baker, 2002;Krieger-Liszkay and Feilke, 2016;Stepien and Johnson, 2018). We first examined the participation of PTOX in a pathway that reroutes electrons from PSII by monitoring the electron transfer rate (ETR PSII ) in the wild type and the ptox2 mutant over a wide range of light intensities.…”
Section: Ptox2 Cannot Compete With Cyt B 6 F-psi For Oxidation Of Thmentioning
confidence: 99%